Typology of Iranian farmers' vulnerability to the COVID-19 outbreak - Moradhaseli, Somayeh; Ataei, Pouria; Karimi, Hamid; Hajialiani, Sara (Frontiers in Public Health, 2022)
Context Presently, farmers are faced with a new crisis caused by the outbreak of COVID-19. On the one hand, they are vulnerable to such respiratory diseases due to the nature of their farming activity. On the other hand, they will definitely be influenced by the pandemic in different aspects no matter if they do not contract the infection. So, this research aimed to study the vulnerability of farmers to the COVID-19 pandemic. Methods The present study was conducted using the quantitative approach and a descriptive-survey methodology. The statistical population was composed of farmers in Kermanshah province, Iran (N = 126,900). The sample (n = 382) was taken by the multistage stratified sampling technique with proportional allocation. The research instrument was a self-designed questionnaire whose face and content validity was confirmed by a panel of relevant experts and its reliability was supported in a pilot test. Results The main damages of the pandemic to the farmers were found to be the increased costs of production, permanent or seasonal unemployment, reduced access to crop sale markets, and reduced control over pests and diseases at farms. The results revealed that the means of environmental, agronomic-vocational, and economic vulnerability were greater than the scale mean. The results also illustrated significant differences in the means of economic, psychological-social, agronomic-vocational, and environmental dimensions of vulnerability. Among these dimensions, the variable of agronomic-vocational vulnerability had the highest mean, and the variable of psychological-social vulnerability had the lowest mean. Conclusion Farmers have been one of the groups most severely influenced and damaged by the pandemic in various aspects. In this regard, organizations and institutions in charge of different agriculture sections, especially the Office of Agricultural Extension and Education, must develop practical strategies to reduce the effect of the pandemic on the agricultural sector. Identifying the dimensions and parameters of farmers' vulnerability in the face of COVID-19 can provide new and appropriate solutions to relevant planners and policymakers.